THE USE OF WORD WALL MEDIA IN THE TEACHING VOCABULARY TO THE SEVENTH GRADE STUDENTS - Wardatuz Zakiyah; Junaidi Mistar; Mutmainnah Mustofa; Dwi Fita Heriyawati (Graduate Program, University of Islam Malang, 2022)
Abstract This study is aimed to know how the teacher using word wall media in teaching of vocabulary at SMPN 30 BATAM, and the students’ perception about the use of word wall media in the teaching of vocabulary. The subject of this study is students of the seventh grade at SMPN 30 BATAM. The method used in this study is phenomenological research. The data collection involved observation, interview, and documentation. The results of the study is indicated that are word wall media is the right medium in mastering vocabulary in teaching vocabulary according to the steps taken by teacher and the most students of seventh grade had positive responds about word wall use in teaching vocabulary at SMPN 30 BATAM. It can be seen based on the word wall wrote down with large letters on the color of a piece paper, it is very interesting and make easy to memorize some difficult vocabularies; and vocabulary mastery can develop by looking for synonym and antonym of that vocabulary; and also the students’ perceptions that word wall media make student more easily to understand some vocabularies. Therefore, the researcher suggests for the English teacher to use word wall media in teaching of vocabulary.Keywords: Vocabulary Mastery, Word Wall Media, Students Perception.